Conversa de senhoras: a performance do feminino em Ana Cristina Cesar - Justino, Katiuce Lopes [UNESP] (2014)
On Ana Cristina Cesar's (1952-1983) poetics, feminine stereotyped discourses and parodies use of textual genders such as correspondences and intimate diaries, produce an ironic effect wherein it is played, in a provocative manner, the relation of the woman herself, transmuted in discourse, to the literary tradition, which has been, throughout History, predominantly masculine. Furthermore, her games with autobiography and the ostensive questionings regarding an identitarian fixity extend the problematization of feminine subject to the problematization of poetry's subjectivity itself. For those reasons and for maintaining a constant and desacralized dialogue with modern tradition, this carioca poet bequeathed to us an original poetic diction, forged by bricolage of dissonant voices, some of them stemming from high literary tradition and others cunningly picked of daily life banality. Giving sustentation for this paper, theories related to modern poetry examination and its origins such as those conducted by HAMBURGUER (2007), BARBOSA (2009) and other German Romanticism related theorists have been performed, in addiction to studies on gender performance fields, such as done by Judith BUTLER (2010), named Gender trouble: feminism and identity subversion, and KLINGER (2007), on performative narrative fields. Ana Cristina Cesar's critical fortune fundamental texts have been read as well.